PENCIPTAAN CAKRAWALA DAN DAMPAKNYA DALAM ILMU PENGETAHUAN DI ERA MILINIAL (Eksegese Kitab Kejadian 1:6-8 dan Mazmur 19:1) - Puji Swismanto (SAGACITY : Journal of Theology and Christian Education, 2022)
The purpose of this research is to foster insight into the development of knowledge about the work of creation of the Charawala in which the side of life that has a major influence on human life has been found, which so far needs to be understood by the quantitative description research method by executing the book of Genesis 1:6-8 and Psalm 19:1 as objects. research.There are many divine mysteries that exist in the early life that need to be recognized so that Christians realize the good impact in life that is on the horizon that has been prepared by the Holy Spirit, which can meet the basic needs of life in the millennial era with the development of Science.The results of the research have a good impact on human life in the millennial era and it is also necessary to have the movement of evil spirits in the air that affects the joints of life like the millennial generation